2D and Trap‐Assisted 2D Langevin Recombination in Polymer:Fullerene Blends. Issue 5 (20th November 2014) - Nyman, Mathias; Sandberg, Oskar J.; Österbacka, Ronald
<x xml:space="preserve">Abstract</x> The impact of trapping on the recombination dynamics in polymer:fullerene blends is clarified using the highly ordered bulk heterojunction (BHJ) blend poly[2, 5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3, 2‐b]thiophene] (PBTTT) and [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) at different weight ratios as a model system. The recombination dynamics are determined using both transient charge extraction and steady‐state techniques. The results show that both the decay of photogenerated charge and the light ideality factor at a polymer:fullerene weight ratio of 1:4 are fully consistent with 2D Langevin recombination; in the 1:1 case the recombination is seen to be affected by electron trapping. The theory of 2D Langevin recombination is extended to the case with high trap density in agreement with the observations in the 1:1 case. The recombination capture coefficients are derived both for trap‐assisted and band‐to‐band recombination and it can be seen that anisotropic charge transport reduces the capture coefficients in both cases resulting in a reduced overall recombination.